Students’ mathematics communication behavior: Assessment tools and their application - Musdi, Edwin; Syaputra, Hamdani; Arnellis; Harisman, Yulyanti (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Mathematics communication ability is an essential component of mathematics that students should have. However, the mathematics communication ability of students, especially in Indonesia, still needs to improve. This study offers a new and different view of mathematics communication to improve it. This study aims to develop an assessment tool for students’ mathematics communication to identify the problems so teachers can focus on improving those areas. Not only the cognitive domain of the students, but this study also includes assessments of the affective and psychomotor domains as well. The reason is that cognitive, affective, and psychomotor aspects are interconnected in mathematics communication. The study of these three domains is called behavior. The assessment tools consist of the mathematics communication behavior analytical rubric and appropriate mathematics test problems. This study is developmental research with three phases: the development of the analytical rubric, the development of mathematics tests, and the application. The participants in this study are two mathematics education experts and 240 students in the 8th grade from seven schools, each located in a different city. The findings of this research show that the developed assessment tools can be used to assess students’ mathematics communication behavior.